Property rights, risk, and livestock development in Africa - Swallow, B.M.; McCarthy, N.; Kirk, Michael; Hazell, Peter B. R. (International Food Policy Research Institute, 1999)
This book documents the proceedings of the international symposium on property rights, risk and livestock Development. It was held to appraise progress, review achievements, and identify remaining research gaps at the conclusion of a three year research project led by the International Livestock Research Institute (ILRI), the International Food Policy Research Institute (IFPRI), and the University of Goettingen. The goal of the project was to support appropriate reforms of property institutions and land policies in the semi-arid areas of sub-Saharan Africa, and the objectives were to better understand how environmental risk affects the use and management of resources under various property rights regimes, to identify circumstances under which different pathways of change in land use and property rights are followed, and to identify how policy and other external interventions can help communities achieve desirable pathways and mitigate negative impacts of undesirable pathways. Topics of discussion include the context for livestock and crop-livestock Development in Africa; modelling of the effects of risk on rangeland management; policies and institutions for risky environments; and empirical studies that include Niger's and Ethiopia's case studies.